1993
DOI: 10.1093/geronj/48.3.p109
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Early Experiences With Parents and Well-being in Old Age

Abstract: This study explores the impact of early experiences with parents on health and well-being in old age. An interview survey was conducted with a representative sample of 267 elderly community residents in the age group 65-74. Standard measures for health, self-esteem, anxiety, depression, and loneliness were included as dependent variables. Quality of parenting was measured by means of a retrospective questionnaire focused on the care dimension of parental behavior. The foremost conclusion of this study is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
71
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 0 publications
4
71
0
4
Order By: Relevance
“…In addition to spouses, the presence of biological children is also associated with lower recalled maternal affection. Whether this is evidence that current social relationships are important in determining how early relationships are (re)interpreted or that early experiences shape current relationship functioning requires longitudinal data ( Andersson & Stevens, 1993 ;Main, Kaplan, & Cassidy, 1985 ).…”
Section: What Individual and Family Factors Predict Variability In Admentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to spouses, the presence of biological children is also associated with lower recalled maternal affection. Whether this is evidence that current social relationships are important in determining how early relationships are (re)interpreted or that early experiences shape current relationship functioning requires longitudinal data ( Andersson & Stevens, 1993 ;Main, Kaplan, & Cassidy, 1985 ).…”
Section: What Individual and Family Factors Predict Variability In Admentioning
confidence: 99%
“…Moreover, studies suggest the domain in which differential treatment occurs has implications for adjustment in childhood (Tucker et al). Most studies of adults' past relationships with parents have been confi ned to memories of affection (e.g., Andersson & Stevens, 1993 ;Rossi & Rossi, 1990 ;Shaw et al, 2004 ) without considering other kinds of experiences, but studies considering adults' memories of problems with parents have found that adults readily recall negative aspects of their relationship experiences ( Amato, 1991 ;Fingerman, 1997 ;Whitbeck, Simons, & Conger, 1991 ). Given the multifaceted qualities of parent-offspring relationships, this study focused on siblings' memories of parental affection, discipline, and confl ict.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
References Andersson, L., & Stevens, N. (1993). Associations between elderly experiences with parents and well-being in old age.

Journal of Gerontology, 48, 109-116.

…”
mentioning
confidence: 99%
“…Most research has focused on parental emotional support, with lower levels of support associated with more physical and emotional problems in older persons. [14][15][16] In addition, loss of a parent in childhood has been related to …”
mentioning
confidence: 99%